FALL RELATED INJURIES: A RETROSPECTIVE MEDICAL REVIEW STUDY IN NORTH INDIA. (7th October 2012) - Jagnoor, J; Keay, L; Ganguli, A; Dandona, R; Thakur, JS; Boufous, S; Cumming, RG; Ivers, RQ
Abstract : Background: Falls have been identified as a leading cause of injury-related morbidity and mortality in India. However, very little is known about the context and characteristics of such falls. Aims/Objectives/Purpose: The aim of this study was to describe the context and characteristics of fall related injuries in patients admitted to hospital for fall injury. Methods: Medical records of patients presenting at the Emergency Department of the Nehru Hospital, Chandigarh, India between March 2008 and February 2009, were reviewed by trained investigators. All injury cases were identified and fall related injury cases were assigned an ICD 10, Chapter XX, External causes of morbidity and mortality code. Results/Outcomes: 10% (7049) of hospital emergency presentations were due to injuries. Falls were the second leading cause (20%, 1407); 76% of fall related presentations were in males. A high proportion (36%) of the fall related presentations occurred in those aged 0–14 years old. Falls from building or structures (35%, 499) were the leading cause for all ages except for those older than 60 years, where same level falls due to slipping, tripping and stumbling (40%, 57) were predominant. Half of all the falls resulted in head injury. Nearly 10% of patients presenting for fall related injury died. Significance/Contribution to the Field: Fall related injuries are an important contributor to hospital emergency presentations. Given the high proportion of falls that resulted in head injury and death, there is a significant need to develop appropriate interventions to prevent such falls.